PENGARUH GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJAANGGOTA POLISI UDARA PADA DIREKTORAT KEPOLISIAN UDARAPONDOK CABE TANGERANG BANTEN - Joko Budiraharjo; Shinta Eria Revina (Sekolah Tinggi Manajemen IMMI, 2019)
Performance within the scope of the organization is the work that has been achieved by an organization in carrying out a job that can be evaluated for its level of performance. The success or failure of the goals and ideals in the organization depends on how the performance process is carried out“The objectives of this research are: 1) For the leadership style at the Directorate of Air Police Pondok Cabe Tangerang; 2) To determine the productivity of air police work at the Directorate of Air Police Pondok Cabe Tangerang; 3) To determine the effect of leadership style on the work productivity of air police officers at the Pondok Cabe Air Police Directorate, Tangerang.“This research has a quantitative approach. The population in this study were members of the Air Police at the Air Police Directorate of Pondok Cabe Tangerang, amounting to 193 members. In this study, the sampling technique used is the Slovin formula. With the Slovin formula technique, a sample of 66 Air Police members at the Pondok Cabe Air Police Directorate, Tangerang.“The results of this study indicate that: 1) the application of leadership style at the Air Police Directorate Pondok Cabe Tangerang is good with an overall average score of 3.41; 2) The work productivity of Air Police Members at the Pondok Cabe Tangerang Air Police Directorate is good with an overall average score of 3,671; 3) the influence of leadership style on the work productivity of Air Police members at the Air Police Directorate Pondok Cabe Tangerang is rxy = 0.646 with a Coefficient of Determination of 41.7%;“Keywords: Leadership Style, Work Productivity.